Generation of Hybrid Optical Trap Array by Holographic Optical Tweezers - Li, Xing; Zhou, Yuan; Cai, Yanan; Zhang, Yanan; Yan, Shaohui; Li, Manman; Li, Runze; Yao, Baoli (Frontiers in Physics, 2021)
Enabled by multiple optical traps, holographic optical tweezers can manipulate multiple particles in parallel flexibly. Spatial light modulators (SLMs) are widely used in holographic optical tweezers, in which Gaussian point (GP) trap arrays or special mode optical trap arrays including optical vortex (OV) arrays, perfect vortex (PV) arrays, and Airy beam arrays, etc., can be generated by addressing various phase holograms. However, the optical traps in these arrays are almost all of the same type. Here, we propose a new method for generating a hybrid optical trap array (HOTA), where optical traps such as GPs, OVs, PVs, and Airy beams in the focal plane are combined arbitrarily. Also, the axial position and peak intensity of each them can be adjusted independently. The energy efficiency of this method is theoretically studied, while different micro-manipulations on multiple particles have been realized with the support of HOTA experimentally. The proposed method expands holographic optical tweezers' capabilities and provides a new possibility of multi-functional optical micro-manipulation.